Discrimination and health: A dyadic approach. (June 2021) - Huynh, Virginia W; Rahal, Danny; Mercado, Evelyn; Irwin, Michael R; McCreath, Heather; Seeman, Theresa; Fuligni, Andrew J
This study examined how discrimination changes over time, how discrimination is related to health and substance use, and whether discrimination spills over to affect the health of family members. Parent–adolescent dyads (N = 341) completed measures of discrimination, physical health, mental health, and substance use over 5 years. Actor–Partner Interdependence Models indicated that individuals' experiences of discrimination can spill over to some aspects of the family context, depending on who is experiencing discrimination (i.e. parent, adolescent) and the outcome (i.e. mental health, substance use). Results suggest that parent-reported discrimination may affect adolescent depression, and adolescent-reported discrimination can spill over to parents' substance use.